ANALISIS ESKALASI IKM BERBASIS DATABASE : UPAYA MENINGKATKAN PEREKONOMIAN DAERAH DAN KESEJAHTERAAN MASYARAKAT - Asas, Istianah; Maulana, Wahyu (Universitas Multimedia Nusantara, 2025)
The urgency of this research lies in the fact that over the past decade, issues related to SMEs in Pamekasan have not been fully resolved. This contrasts with the government's current focus on the larger creative economy sector. This relates to the incomplete and uneven distribution of SME database (NIB) data collection. This fundamental problem impacts the ability of SMEs to move up a class to the difficulty of monitoring SMEs so that decision making becomes wrong/not in accordance with the target. The novelty of this study lies in the focus of research on database-based SMEs (NIB) problems by using QDA Miner Lite as an analysis and data processing tool. The study population was 107 with a sample of 39 SMEs using a purposive sampling technique. The type of qualitative research and research methods were interviews and field surveys. The results of the study indicate that Pamekasan SMEs whose NIB is problematic are caused by the SME factor not fully understanding how to update an inactive NIB, while for the most escalated SMEs, namely Pamekasan SMEs, their businesses continue to grow so they can survive in the existing competition to improve the regional economy. The implications of this research for the Pamekasan district government are to pay more attention to problematic SMEs in terms of NIB which is a regional government database so that it is easier to conduct evaluations, monitoring and implement escalation programs that are more targeted for the welfare of Pamekasan SMEs and improve the regional economy